Global outsourcing and offshoring : an integrated approach to theory and corporate strategy - Contractor, Farok J., editor; Kumar, Vikas, editor; Kundu, Sumit K., editor; Pedersen, Torben, editor (Cambridge, UK ; New York : Cambridge University Press, 2011)
Includes bibliographical references and index